KEEFEKTIFAN KALIMAT DALAM TEKS EKSPLANASI SISWA KELAS VIII SMP PEMBANGUNAN LABORATORIUM UNP - Syukur, Mita; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study is to describe the sentences in the explanatory text of students in terms of four things. First, the effectiveness of sentences in terms of structural clarity, there are 78 (19.60%) errors. The ineffectiveness of the sentence is in the active / passive structure (1 error), the subject is not an explanation (21 errors), the predicate is not lost (28 errors), the description is not in the form of a subject (4 errors), and the subject is not lost (25 errors). Second, the effectiveness of sentences in terms of logical meaning there are 76 (19.09%) errors. The ineffectiveness of the sentence lies in the logical relationship S and P (52 errors) and the logical relationship of details or parallel meaning (23 errors). Third, the effectiveness of sentences in terms of word saving is 142 (35.68%) errors. The ineffectiveness of the sentence is on one subject from the same subject (46 errors), one word from several synonymous words (21 errors), and the required word (115 errors). Fourth, the effectiveness of sentences in terms of word rigidity there are 102 (25.63%) errors. Based on these results it can be concluded that the sentences in the explanatory text of eighth grade students of SMP Pembangunan Laboratorium Laboratory are not effective. This is evidenced from the 221 sentences studied, there were 31 (14.03%) effective sentences and 190 (85.97%) ineffective sentences with 398 errors. Kata kunci: Keefektifan Kalimat, Teks Eksplanasi